PENGARUH PERENCANAAN PAJAK, THIN CAPITALIZATION DAN RASIO UTANG TERHADAP NILAI PERUSAHAAN - Maria Inviola Trida; Sutandijo (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to determine the effect of tax planning, thin capitalization, and the debt ratio on firm value. The population in this study was all property and real estate companies listed on the Indonesia Stock Exchange in 2019-2024. The sample used in this study was determined using a purposive sampling method, with predetermined criteria, resulting in a sample of 10 companies. The data used in this study were secondary data in the form of annual reports and audited financial statements of property and real estate companies listed on the Indonesia Stock Exchange in 2019-2024. This research is quantitative. The data analysis technique used multiple linear regression analysis with the help of Eviews version 12. The results of this study indicate that simultaneously, tax planning, thin capitalization, and the debt ratio have an effect on firm value. Meanwhile partially Debt Ratio does affect firm value, but tax planning and Thin capitalization does not affect firm value.